2014
DOI: 10.2190/ec.50.1.f
|View full text |Cite
|
Sign up to set email alerts
|

Instruction of Statistics via Computer-Based Tools: Effects on Statistics' Anxiety, Attitude, and Achievement

Abstract: The purpose of this study was to determine the effect of statistics instruction using computer-based tools, on statistics anxiety, attitude, and achievement. This study was designed as quasi-experimental research and the pattern used was a matched pre-test/post-test with control group design. Data was collected using three scales: a Statistics Anxiety Rating Scale, a Statistics Attitude Scale, and a Statistics Achievement Scale. ANCOVA and MANCOVA analyses the used during the analysis process. The findings of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
0
14
0
1
Order By: Relevance
“…a replica of conventional lecture method utilized in this study. The efficacy of the computer-aided teaching strategy was further confirmed by Ciftci et al (2014) who discovered computer-based tools statistics instruction (i.e. a variant of computer-aided teaching) had a considerable and beneficial effect on statistics achievement, with the eta square values from the Analysis of Covariance results showing a high magnitude of the effect, and supporting results of the statistics attitude post-test scores.…”
Section: Discussionmentioning
confidence: 75%
“…a replica of conventional lecture method utilized in this study. The efficacy of the computer-aided teaching strategy was further confirmed by Ciftci et al (2014) who discovered computer-based tools statistics instruction (i.e. a variant of computer-aided teaching) had a considerable and beneficial effect on statistics achievement, with the eta square values from the Analysis of Covariance results showing a high magnitude of the effect, and supporting results of the statistics attitude post-test scores.…”
Section: Discussionmentioning
confidence: 75%
“…Because learning new statistical software is consistently a challenging component of this course, it is anticipated that continued use of lab time to teach the software will increase the approachability of the class. There is justification for this expectation based on the findings of Ciftci et al who showed that the use of computer instruction reduced the level of anxiety on the part of students and improved their general opinion of statistics (Ciftci, Karadag, & Akdal, 2014). Even other statisticians have made calls for inclusion of more computational components to statistical instruction (Cobb, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the value placed on the courses by the instructors of higher education, few students eagerly anticipate taking a course in statistics (Stork, 2003). In fact, once in the course, students often find the course tedious and difficult and approach them with a level of fear (Stork, 2003) (Ciftci, Karadag, & Akdal, 2014). Furthermore, students express doubt about the applicability of stats to real-world usage (Wells, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is supported by (Chiesi, Primi, & Carmona, 2011) stating that good self-concept in high statistical and intrinsic value positively affects achievement and reduces statistical fears. Computer-based statistics teaching also reduces statistical concerns and increases statistical performance (Ciftci, Karadag, & Akdal, 2014). This may be due to students understood better statistical functions and applications through computer-based learning than traditional learning and this understands statistical fears.…”
Section: Relationship Between Statistical Anxiety and Achievementmentioning
confidence: 99%